ESTUDIO DE LA COMERCIALIZACIÓN DE TECNOLOGÍA GENERADA DESDE LAS UNIVERSIDADES NACIONALES - Fairlie Frisancho, Ebor (2012)
The study focused on examining technology made by Public Universities. UNMSM, UNFV, UNSCH, UNI were tested for being in contact with all of them, and it is seen that only UNMSM and UNI have research in faculties like medicine, veterinary and engineering and with a research record. To take advantage, it must have a process of adjustment and institutional learning, thus filling the gaps that currently preventeffectively and efficiently exploit the intellectual property generated by research activities. This research has identified factors such as lack of patents, licenses, production areas and especially in the marketing process. Official policies are being suggested regarding technology transfer research both as academics and administrative and resource generationby the University to Faculties in order to help enterprises alliances with national and international companies.